A Performance-Based Approach to Safety Management: Mapping Safety Indicators and Targets in Multi-Approval Training Organizations - Dwi Lestary; Elfi Amir; Akbar Hidayatullah; Direstu Amalia (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Safety Management Systems (SMS) are formally required across aviation training organizations; however, institutions holding multiple operational approvals frequently encounter difficulties in translating regulatory requirements into coherent and measurable safety performance indicators and targets. In practice, safety performance monitoring is often fragmented, approval-specific, and insufficiently aligned with a performance-based oversight philosophy. This study addresses this gap by examining how safety indicators and targets can be systematically mapped within a unified SMS framework for multi-approval aviation training organizations. This research adopted a qualitative design-based approach, combining document analysis, internal stakeholder interviews, comparative benchmarking with peer training organizations, and focus group discussions involving regulators, operators, and safety managers. Data triangulation was applied to ensure consistency and analytical validity throughout the framework development process. The results demonstrate that safety performance expectations differ substantially across approvals due to distinct operational risk characteristics. Nevertheless, these differences can be integrated through a common safety assurance structure without compromising regulatory specificity. The study identifies approval-specific safety performance indicators and targets for pilot training, aircraft maintenance, and maintenance training activities, and shows that an integrated performance-based mapping improves safety oversight, strengthens compliance mechanisms, and enhances organizational accountability. From a theoretical perspective, this study extends performance-based safety management literature by situating safety performance measurement within a multi-approval governance context. Practically, it offers aviation training organizations and regulators a structured and adaptable framework for harmonizing safety performance monitoring across approvals. The study contributes a transferable model that supports resilient and performance-oriented SMS implementation in complex aviation training environments.